NH4+ Fixation and Ionic Competition with K+ in a Clayey Soil from Ocumare Del Tuy, Venezuela - Lopez-Hernandez, Danilo; Mahia-Masip, Miguelangel; Melendez, Williams; Lopez-Contreras, Ana (Canadian Journal of Agriculture and Crops, 2022)
Ammonium and potassium are essential for plant production, both share an ionic potential capable of entering the structure of some 2:1 type clay minerals, remaining fixed. Although, in Venezuela there are abundant areas with the presence of this type of clays, ammonium fixation (NH4f) has been little studied. The soil studied located in Los Valles del Tuy, Miranda State, presented clayey texture, some textural homogenization, and little differentiation in horizons, which is characteristic of Inceptisols. That soil also evidenced by XRD the abundant presence of nontronite / montmorillonite, resulting in a semi-quantification of 20% and 16.4% for the surface and subsoil horizons, respectively. The fixation of ammonium and the competition with potassium to occupy the fixed sites of these clays were studied by means of an incubation experiment, varying the concentration of K+ and keeping the concentration of NH4+ fixed, then extracting and determining the fixed ammonium by a photocolorimetry method. The soil presented a great ammonium fixing capacity, 49% of the total added was fixed in the absence of the competitive ion; however, NH4f fell drastically when both ions were added simultaneously, decreasing exponentially under increasing amounts of the competitive ion and staying constant around 8%. It seems possible that, the high toxicity induced by excessive fertilisation with ammonium sulfate could be counteracted in soils with capacity to retain K, if, at the expense of Kf, the levels of K in the soil solution are increased causing a decrease in the concentrations of N in the tissue.